2019
DOI: 10.1167/tvst.8.3.62
|View full text |Cite
|
Sign up to set email alerts
|

Fundus-Controlled Dark Adaptometry in Young Children Without and With Spontaneously Regressed Retinopathy of Prematurity

Abstract: Purpose: We correlate dark adaptation course with foveal morphologic alterations in preterm and term-born children using a modified fundus-controlled perimeter and spectral domain-optical coherence tomography (SD-OCT) imaging. Methods: We performed fundus-controlled chromatic dark adaptometry in premature children aged 6 to 13 years without retinopathy of prematurity (no-ROP; n ¼ 61) and with spontaneously regressed ROP (sr-ROP, n ¼ 29), and in 11 age-matched term-born children. The degree of macular developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…3 Despite the availability of this therapy, many children with a history of ROP suffer visual impairment, including reduced visual acuity and deficient subtle color vision, 4 constricted visual field and contrast sensitivity, 5 and increased dark-adapted thresholds. 6 Moreover, human 7,8 and animal studies 9,10 have shown retinal dysfunction and structural abnormalities. The aforementioned evidence strongly implies that the neural retina is also affected by ROP.…”
Section: Introductionmentioning
confidence: 99%
“…3 Despite the availability of this therapy, many children with a history of ROP suffer visual impairment, including reduced visual acuity and deficient subtle color vision, 4 constricted visual field and contrast sensitivity, 5 and increased dark-adapted thresholds. 6 Moreover, human 7,8 and animal studies 9,10 have shown retinal dysfunction and structural abnormalities. The aforementioned evidence strongly implies that the neural retina is also affected by ROP.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Wadim Bowl and coworkers proposed the only other protocol for fundus-controlled dark adaptometry. 27 , 28 However, due to limitations of the MP1 microperimeter, their protocol necessitated adding filters to the optical path and changing the stimulus size during the examination to compensate for the low dynamic range. In addition, each test run had to be initiated manually, and no inter-device validation or retest reliability data were published for their method.…”
Section: Discussionmentioning
confidence: 99%
“…To address these shortcomings, using the MP1 device has been proposed for fundus-controlled dark adaptometry. 27 , 28 However, due to the limited dynamic range of the device, this method necessitated adding optical filters and changing the stimulus size within test runs. Additionally, the workflow was also not fully automated, hindering its application in multicenter therapeutic trials.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, most literature focuses on the mechanisms leading to neovascularization and the current therapeutic treatments are directed to the normalization of the retinal vasculature [ 99 ]. However, despite the effectiveness of these treatments or the spontaneous regression of the pathology, many children with a history of ROP experience persistent vision impairment, such as astigmatism and myopia [ 100 ], reduced visual acuity and deficient subtle color vision [ 101 ], constricted visual field and contrast sensitivity [ 102 ], and increased dark-adapted thresholds [ 103 ], along with structural retinal abnormalities [ 4 , 104 ]. Overall, these data suggest that some form of alteration in the development, viability, and function of neuroretinal cells (photoreceptors, retinal neurons and glia), may occur during ROP progression ( Figure 2 ).…”
Section: The Impact Of Rop In the Central Nervous Systemmentioning
confidence: 99%